Analisis Lapangan Usaha Unggulan Kabupaten Majalengka dengan LQ dan DLQ ANALYSIS - Sukmono , Renny; Suci Pramadani, Tiara (Universitas Negeri Surabaya, 2023)
The government needs an easy and simple analytical tool in determining development priorities, especially in the economic sector. The government needs to compile business fields which are development priorities to be developed first. Several alternative analysis tools are available, including LQ analysis and DLQ analysis. The Majalengka government is one of the centers of attention because this district is one of the districts as the location of Indonesia's new international airport. Of course there is a reason why Majalengka Regency is the location of Indonesia's new international airport. Based on LQ descriptive statistics, in general Majalengka Regency is one of the regencies that are able to meet their own needs and are able to export to other regions. However, this ability is decreasing from year to year. The field of agricultural business is still a priority. However, the results of the simultaneous analysis of the LQ and DLQ methods show that the agricultural business field has the potential to become a supporting sector in the future. The mining business sector and the financial services and accounting business sector are two leading business fields and have the potential to continue to be superior in the future.